Tourism and SME businesses opportunity in Lenggong Valley World Archaeological Heritage Site Malaysia - Mhd Rashid, Munira; Jaafar, Mastura; Dahalan , Norziani (2013)
Tourism and Small and Medium Enterprises (SMEs) have been proven to have impact on economic country development. In order for tourism to be advantageous in terms of economic development, income earning, poverty diminution, and improving rural livelihoods, it should be associated with the local economic activities. Business activities in tourism or tourism SMEs are typically involved with activities providing demands and needs of tourists such as food, accommodation, transportation and other necessities.The objective of this study is to understand the potential of tourism activities and SMEs businesses opportunity in Lenggong Valley, Perak. The declaration as World Archaeological Heritage Site by United Nations Educational, Scientific, and Cultural Organization (UNESCO) has opened a huge opportunity for Lenggong Valley to be a world attractive tourism site for its historical value and natural resources. With high level of local community readiness, tourism and SMEs in Lenggong Valley has the potential to be developed. Nonetheless, all the stakeholders must be able to apply appropriate strategy and tactics in order to make Lenggong Valley become a marketable and attractive place for both local and international tourists.